2019
DOI: 10.1093/ofid/ofz405
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Coverage vs Frequency for Sexually Transmitted Infection Screening of Men Who Have Sex With Men

Abstract: Background The incidence of bacterial sexually transmitted infections (STIs) in men who have sex with men (MSM) has increased substantially despite availability of effective antibiotics. The US Centers for Disease Control and Prevention (CDC) recommends annual screening for all sexually active (SA) MSM and more frequent screening for high-risk (HR) MSM. The population-level benefits of improved coverage vs increased frequency of STI screening among SA vs HR MSM are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Previous analyses have demonstrated the expected effects of increased NG/CT screening on NG/CT incidence 20 ; our analysis expands on those results to understand the effects of NG/CT screening on HIV incidence. There is strong evidence for the synergy between the HIV and STI epidemics among MSM, including shared transmission mechanisms and risk factors 3,4 .…”
Section: Discussionmentioning
confidence: 60%
“…Previous analyses have demonstrated the expected effects of increased NG/CT screening on NG/CT incidence 20 ; our analysis expands on those results to understand the effects of NG/CT screening on HIV incidence. There is strong evidence for the synergy between the HIV and STI epidemics among MSM, including shared transmission mechanisms and risk factors 3,4 .…”
Section: Discussionmentioning
confidence: 60%
“…5 Finally, modelling studies have reached various conclusions. For example, one study found that screening MSM could approximately halve the incidence of CT/NG 14 whilst another found screening would have a minimal effect on CT/NG prevalence and result in a large increase in antimicrobial consumption. 15…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al [49] implemented a model that fully parametrizes the effect of an STI on HIV transmission to study chlamydia and gonorrhea screening and treatment. However, the model doesn’t implement the effect of HIV on STI transmission, while Simpact Cyan 1.0 does.…”
Section: Discussionmentioning
confidence: 99%